Cake layer bacterial communities during different biofouling stages in full-scale membrane bioreactors. (July 2018) - Takada, Kazuki; Shiba, Toshihiko; Yamaguchi, Takako; Akane, Yui; Nakayama, Yoshinari; Soda, Satoshi; Inoue, Daisuke; Ike, Michihiko
Graphical abstract: Highlights: Cake layer bacterial communities in full-scale MBRs were analyzed. Unique compositions were found, especially after TMP jump and transitional phase. Firmicutes members made a major contribution throughout biofouling process. Certain key candidate bacteria associated with biofouling were identified. Abstract: A detailed understanding of the bacterial communities in the cake layers formed on the membrane surface is required to control biofouling in a membrane bioreactor (MBR). This study aimed to investigate the dynamics of the cake layer bacterial communities in full-scale MBRs operated in a wastewater treatment plant in Japan and to identify the key bacteria responsible for cake layer formation. The bacterial communities in the cake layer and the activated sludge were analyzed using 16S rRNA gene amplicon sequencing when biofouling occurred under different fouling conditions. The most dominant phyla in activated sludge were almost always Proteobacteria and Bacteroidetes . By contrast, when the cake layer had unique bacterial communities distinguishable from those in the activated sludge, members of Firmicutes were highly dominant in the cake layer, irrespective of the fouling conditions. This study reported for the first time that Firmicutes play an important role throughout the biofouling process.